Infectious complications in acute myeloid leukemia patients (Actualizaciones en Sida e Infectología, 2018)
Acute leukemias have been recognized as complex and radiply fatal diseases since its rst description 150 years ago. Delivered to its natural history, acute myeloid leukemia leads to death in a few months. Infections are the main cause of death, being bacteremia and pneumonia the most frequent. Advances in the last 50 years, such as the advent of effective chemotherapy, a best understanding of the pathogenesis of infectious complications in the neutropenic patient, the availability of broad-spectrum anti-infective agents and better supportive care helped improve this situation. Among other oncological diseases, acute myeloid leukemia has the highest incidence of febrile events, being induction to remission the period of greatest risk. Fever of unknown origin, bacterial multidrug resistance and invasive fungal infections are a challenge for the medical team. The use of antibacterial and antifungal prophylaxis does not replace institutional preventive measures.
Keywords: acute myeloid leukemia; febrile neutropenia; antibiotic prophylaxis/utilization; antifungal prophylaxis